Karst hydrogeology, geomorphology, and caves - Waele, Jo De; Gutierrez, Francisco (Wiley, 2022)
The last decade witnessed the meteoric rise of Chinese tech players, especially the internet firms, which rely on (mobile) internet as the main distribution channel to reach out to hundreds of millions of customers, and use internet-enabled technologies, such as logistics, supply chain management, credit assessment and cloud computing, to serve customer demands, and reform/disrupt traditional industries. These Chinese firms not only include the well-known giants, such as Alibaba, Tencent, and ByteDance (parent of TikTok), but also many others who are worth tens of billions but still under the radar of global business communities, such as SheIn, Transsion, J&T express. These firms have collectively built a formidable presence in every aspect of life across cities in China over a few years. As growth in China slows down, and competition further intensifies, these giants are increasingly setting their sight on the global markets. Despite early mistakes and setbacks by a few large firms, including Baidu and Alibaba, waves of Chinese companies, armed with capital, experience, and talent, are expanding in different regions across the globe, copying each other's successes and learning from each other's failures."--